The metabolism of 5-hydroxytryptamine and beta-phenylethylamine in perfused rat lung and in vitro. - Bakhle, Y S (1979)
1 Metabolism of 5-hydroxytryptamine (5-HT) and beta-phenylethylamine (PHE) by monoamine oxidase (MAO) was investigated in rat isolated lungs and in mitochondrial preparations from rat lung. 2. In perfused lungs 5-HT metabolism had an apparent Km of 2 microgram and PHE metaoblism a Km of 54 microgram, whereas in vitro the Km values were 330 microgram and 28 microgram respectively. 3 In vitro, MAO activity had substrate and inhibitor specificities compatible with the presence of A and B types of MAO. 4 In perfused lung, metabolism of 5-HT but not that of PHE was inhibited by desmethylimipramine. 5 These results show that PHE metabolism in perfused lung, unlike that of other metabolized amines, is not limited by transport and the transport process for PHE is unlike that of 5-HT or noradrenaline. 6 These results also show that the kinetic parameters obtained for MAO activity in vitro do not generally apply to the isolated lung where transport of substrate can be the deciding factor. This discrepancy emphasizes that the enzymic properties of the whole organ cannot relaibly be deduced from its enzymic content.